RE Flow With Prototype & Its Impact with End- user in System Development (International Journal of Engineering and Computer Science, 2017)
This paper generally focuses on different aspects of techniques related to requirement gathering as well as why and how these techniques may help stakeholder and the system for development. The main entity in SDLC is a customer/ stake holder. As the customer is the one for whom any project is built up or any IT company works, it is mandatory to keep them satisfied by providing them accurate solution of their problem. The paper is about the explanation of different majorly used requirement gathering techniques and their importance. From this paper, one can get idea which technique is suitable in various environments.